2021
DOI: 10.3390/sym13030459
|View full text |Cite
|
Sign up to set email alerts
|

Heat Driven Flows in Microsized Nematic Volumes: Computational Studies and Analysis

Abstract: The nematic fluid pumping mechanism responsible for the heat driven flow in microfluidic nematic channels and capillaries is described in a number of applications. This heat driven flow can be generated either by a laser beam focused inside the nematic microvolume and at the nematic channel boundary, or by inhomogeneous heating of the nematic channel or capillary boundaries. As an example, the scenario of the vortex flow excitation in microsized nematic volume, under the influence of a temperature gradient cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…By means of other hydrodynamic flow with profiles, which cannot demonstrate the sharp growth of u st across the HAN channel, one can achieve the same result only by using of the "high-speed" hydrodynamic flow ∼0.1 µm/s [22]. However, taking into account that some LC systems driven by external SS exhibit such non-equilibrium phenomena as a tumbling behavior [7,8,23], the mechanical description can shed some light on the problem of temperature gradient formation; when under certain conditions, the thermomechanical force can overcome elastic, viscous, and anchor forces and cause a temperature gradient across the HAN channel.…”
Section: Shear-driven Flow Regimes In Microfluidic Nematic Devices: T...mentioning
confidence: 99%
See 4 more Smart Citations
“…By means of other hydrodynamic flow with profiles, which cannot demonstrate the sharp growth of u st across the HAN channel, one can achieve the same result only by using of the "high-speed" hydrodynamic flow ∼0.1 µm/s [22]. However, taking into account that some LC systems driven by external SS exhibit such non-equilibrium phenomena as a tumbling behavior [7,8,23], the mechanical description can shed some light on the problem of temperature gradient formation; when under certain conditions, the thermomechanical force can overcome elastic, viscous, and anchor forces and cause a temperature gradient across the HAN channel.…”
Section: Shear-driven Flow Regimes In Microfluidic Nematic Devices: T...mentioning
confidence: 99%
“…It has been shown that, due to the temperature gradient ∇T, the horizontal hybrid aligned nematic (HAN) microfluidic channel, being initially at rest, starts moving in the horizontal direction if heated from below or above [6][7][8]. In the case when the director n is anchored homeotropically to the cooler (T lw ), lower boundaries and homogeneously to the hotter (T up ) upper boundaries, due to coupling between ∇T ∼ ∆T d and ∇ n, the hydrodynamic flow v = v x î = u î [7] in the horizontal direction is excited.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations